The fundamentals for craniofacial morphogenesis -A review with emphasis on the decisive dynamics - Gaurav Agnihotri (Wolters Kluwer Medknow Publications, 2018)
A rekindled need to understand details of craniofacial morphogenesis stems from the clinicians requirement to distinguish normal variation from the effect of abnormal or pathologic processes. The understanding of the developmental blueprint is core to diagnosis, timing, planning of treatment and predicting post treatment outcomes. The morphogenesis works constantly towards a state of composite, architectonic balance among all of the separate growing parts. The various parts, developmentally merge into a functional whole with each part complementing the others as they all grow and function together. The present overview takes into account the principal fundamentals of the morphogenesis and the decisive dynamics involved therein. There is a cephalo- caudal gradient in the craniofacial growth pattern. In accordance with functional matrix theory, the major determinant of growth of maxilla and mandible is enlargement of nasal and oral cavities, which grow in response to functional needs. The craniofacial complex can be divided into four areas that grow rather differently.These are cranial vault, cranial base, nasomaxillary complex and mandible. The craniofacial morphogenesis leads to an aggregate state of structural and functional equilibrium. A thorough understanding of the process and patterns is the 'vital key' for successful therapies in this region.